PENYERAPAN LAPANGAN KERJA LULUSAN JURUSAN SOSIOLOGI DAN ANTROPOLOGI FIS UNNES ANGKATAN 2001-2003 (Forum Ilmu Sosial, 2008)
The absorption of graduates in opportunities of employment that match with their discipline is oneindicator of the education institution success. Seeking the absorption of Sociology and AnthropologyStudy Program graduates in opportunities of employment is much needed. Most of the Sociology andAnthropology Study Program graduates are become teacher, both in state or private school. Beside becometeacher, they work in non education field, such as in bank, in hospital, etc. To access job opportunities,Sociology and Anthropology Study Program graduates seek the information through asking friend, internetmedia, mass media, and trial and error method.Keywords: Absorption, graduates, job opportunity